If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -9 = 3(p + 5) Reorder the terms: -9 + 7p = 3(p + 5) Reorder the terms: -9 + 7p = 3(5 + p) -9 + 7p = (5 * 3 + p * 3) -9 + 7p = (15 + 3p) Solving -9 + 7p = 15 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. -9 + 7p + -3p = 15 + 3p + -3p Combine like terms: 7p + -3p = 4p -9 + 4p = 15 + 3p + -3p Combine like terms: 3p + -3p = 0 -9 + 4p = 15 + 0 -9 + 4p = 15 Add '9' to each side of the equation. -9 + 9 + 4p = 15 + 9 Combine like terms: -9 + 9 = 0 0 + 4p = 15 + 9 4p = 15 + 9 Combine like terms: 15 + 9 = 24 4p = 24 Divide each side by '4'. p = 6 Simplifying p = 6
| 3=3(u+5)-7u | | 8(3w+9)=2 | | 0.7(3y+6)=0 | | 1x+3=-7x-25 | | -2(2t+4)=0 | | 8=13-3y-4 | | 11-y=0 | | 3x-4=(x-4) | | 12-y=-6 | | r+0.5r=1650 | | X^2-xk+3x-4=0 | | c+3c+2=5c-1 | | x+0.25x=43 | | 2x-3=5x-3x-3x | | 22.8-9p=8p+2.4 | | 4(2m-5)=28 | | 38700+x-.01x-223939=50000 | | 9k+4.2=k+8 | | -9y+4y-2= | | F-8=-3f | | z-14=-1 | | 22.4-9p=8p+2.4 | | 5x^3+6x^2+3x+14=x+1 | | -3b+2=4b-12 | | z+8=25 | | z+11=28 | | 3x+9-2x= | | 5x+12-4x+3=12 | | 3x-1=6x-4 | | 2^7/6-14=0 | | z+18=28 | | 1000.00/.35 |